Pemberdayaan Kader Posyandu Balita Dalam Pencegahan dan Penanganan Balita Stunting Dengan Akupressure dan PMT Pemulihan Pangan Lokal Di Wilayah Kerja Puskesmas Bendo - palupi, mirthasari (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2024)
Stunting is where the condition of failure to thrive in children under 2 years is caused by malnutrition for a long time (chronic). This can have a devastasting impact on a child’s physical and psychological well-being. Therefore, this activity is carried out, to provide good nutrition for toddlers by conducting a Recovery Supplementary Feeding (PMT) program with Acuppresure which is carried out in the working area of the Bendo Health Center. The active role of cadres in this regard is also needed to maintain the continuity of this program. A total of villages with 27 integrated healthcare center and 140 cadres under five in the working area of the Bendo Health Center. The method carried out is in the form of providing counseling through technology transfer, creating PMT menus, recorvery with local food ingredients, and transferring acupressure technology to integrated healthcare center cadres under five wich is carried out in each village in rotation in the Bendo Health Center work area. The result of the activity showed an increase in knowledge, skills and creative cadres in compiling recovery PMT menus with local food ingredients and skilled in acupressure for toddlers. From this activity, it is expected to help prevent stunting in the Bendo Health Center work area and the active role of cadres in stunting prevention.